Long-Run Money Demand in Large Industrial Countries. (IMF Working Papers; Working Paper, 1990)
The reputation of the aggregate demand function for money balances has plummeted since the mid-1970s, owing to the destabilizing effects of financial innovation and deregulation. There is, nonetheless, a renewed effort among economists to uncover stable relationships, a revival that reflects in part the development of new econometric approaches, especially those related to cointegration and error correction models. This paper examines the long-run properties of money demand functions in the large industrial countries, under the hypothesis that the long-run functions have been stable but that the dynamic adjustment processes are more complex than those represented in most earlier models. The results do broadly support this hypothesis, but for certain aggregates they also call into question some basic hypotheses about the nature of the demand function, including notably that of homogeneity with respect to the price level.